AN ABUNDANCE OF SEMI-ABSTRACTION IN INDIAN PAINTING - Singh, Manjeet (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Since ancient times, semi-abstraction has been found in the form of stylization of natural and geometrical motifs employed on any artefact or any other expression of art. The earthen wares excavated from Harappa, the capitals from the Mauryan Period, and the railing and toranas from Sanchi are the legacy of Indian art in the form of stylized sculptures and relief works. Which have survived after the ravages of ages and natural calamities. Keeping aside the murals of the Ajanta caves, the painting as a perishable form of art has been found since only the Pala and Jaina periods. Since then, stylization has been abundantly used in every style as an integrated feature of Indian Art. Semi-abstraction is the middle stage of any modification from real to fully abstract form. The unique style of Kishangarh, Ragmala series from Mewar, the depiction of themes from Gita Govinda of Jaidev, and female figures from the Basoli, Kangra, and Garhwal present examples of semi-abstraction and stylization. During the modern art movement of the 20th century, the renowned artist named Jaimin Roy has excelled in this traditional technique of semi-abstraction and stylization. This study shows how the semi-abstraction works and how it is used. Understanding its limitations is a very necessary part of keeping the semi-abstract and stylized artwork graceful. This study also throws light on the use of idealism in semi-abstract or stylized art. Contrary to Naturalism’s hardships for perfect resemblance, Indian artist has been mainly concerned with the soul of the subject matter.